Hypoglycemia and the risk of cognitive impairment and dementia in elderly and senile patients with type 2 diabetes - Olga D. Ostroumova; Elena V. Surkova; Irina V. Goloborodova; Antonina V. Starodubova; Alexey I. Kochetkov; Tamara D. Kiknadze; Gagik R. Galstyan (Сахарный диабет)
Research results show that poor glycemic control and recurrent episodes of severe hypoglycaemia are associated with a decrease in cognitive function in elderly people with type 2 diabetes mellitus (T2DM). On the other hand, patients with diabetes mellitus associated with cognitive impairment/dementia are most at risk of developing hypoglycaemic conditions. It is obvious that the relationship between hypoglycaemia and dementia is very complex and has a mutually aggravating nature. Studies also show that individuals of older age groups with diabetes and cognitive impairment have a high risk of developing hypoglycaemic conditions, such as unwanted side effects from glucose-lowering therapy. In this case, of particular interest is the question that is being actively studied at the present time, which is concerning the effect of different groups of glucose-lowering antidiabetic drugs on the cognitive status and the rate of cognitive decline in diabetic patients with cognitive impairment. In this review, we attempted to summarise, systematise, and present data available in the literature concerning the effect of hypoglycaemia on the risk of cognitive impairment and dementia in elderly and senile patients with type-2 diabetes, as well as the degree of participation in this process of of various groups of sugar-lowering antidiabetic drugs.